Clinical impact of detection of loss of heterozygosity of BRCA1 and BRCA2 markers in sporadic breast cancer. - Beckmann, M. W. (Nature Publishing Group, 1996)
The development of familial and sporadic breast cancer is based on genetic alterations of tumour-suppressor genes, for which loss of heterozygosity (LOH) is one mechanism of gene inactivation. To investigate LOH of BRCA1 (17q21) and BRCA2 (13-q12-13) in sporadic breast cancer, polymerase chain reaction (PCR)-based fluorescent DNA technology for detection of microsatellite polymorphisms was applied. A total of 137 breast cancer and 15 benign breast specimens with matched normal tissue were examined. Fluorescent-labelled PCR products were analysed in an automated DNA sequencer (ALFTM Pharmacia). Losses at both loci were correlated with different histological types, age, tumour size, lymph node status, grading and steroid hormone receptor expression, [SHR: oestrogen receptor (ER), progesterone receptor (PgR)]. For BRCA1 (D17S855, THRA1, D17S579) losses could be detected in invasive ductal carcinoma (IDC; n = 108) in 32-38%, invasive lobular carcinoma (ILC; n = 19) in 21-42% depending on the marker applied, but not in benign breast tumours (n = 15). Losses of BRCA1 markers correlated with larger tumour size, higher grade, and PgR expression. For BRCA2 (D13S260, D13S267, D13S171) losses could be detected in 108 IDCs in 30-38%, in 19 ILCs in 17-39% depending on the marker applied, but not in benign breast tumours. Losses of BRCA2 markers correlated only with higher grade. Microsatellite analyses combined with detection of fluorescent-labelled PCR products by an automated laser DNA sequencer can be used for routine determination of LOH. In sporadic breast cancer, LOH of BRCA1 of BRCA2 does not add decisive prognostic value as stated for familial breast cancer. IMAGES: